2020
DOI: 10.1016/j.cell.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Calprotectin and Abnormal Myeloid Cell Subsets Discriminate Severe from Mild COVID-19

Abstract: Highlights d Patients with severe COVID-19 accumulate HLA-DR Low monocytes and immature neutrophils in blood/lungs d Calprotectin level positively correlates with neutrophil count and disease severity d Loss of non-classical monocytes could identify high risk of severe COVID-19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

137
980
8
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 738 publications
(1,172 citation statements)
references
References 71 publications
137
980
8
7
Order By: Relevance
“…Interestingly, we also found an upregulation of cytoplasmic S100A9 in monocyte subsets specifically amplified in COVID-19 patients irrespectively of their ARDS status. These data suggest that, in the early stage of the disease, monocytes could contribute to the burst of circulating calprotectin (S100A8/S100A9), recently proposed to contribute to the secondary cytokine release syndrome described in severe COVID-19 and attributed to neutrophils (18).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Interestingly, we also found an upregulation of cytoplasmic S100A9 in monocyte subsets specifically amplified in COVID-19 patients irrespectively of their ARDS status. These data suggest that, in the early stage of the disease, monocytes could contribute to the burst of circulating calprotectin (S100A8/S100A9), recently proposed to contribute to the secondary cytokine release syndrome described in severe COVID-19 and attributed to neutrophils (18).…”
Section: Discussionmentioning
confidence: 61%
“…The amplification of CD169 pos circulating monocytes has already been highlighted in the context of COVID-19 (11,18,36,37), and is reminiscent of other inflammatory conditions found in viral infections, such as with Human Immunodeficiency Virus or Epstein-Barr Virus, in which the CD169 sialoadhesin is induced in an IFN-dependent manner on the surface of circulating monocytes (38,39). Consistent with the inflammatory response, we showed that the accumulation of CD169 pos monocytes in COVID-19 pos patients is positively correlated with an increase of plasmablasts and mature plasma cells, Th1-like CD8 effector T cells, cytotoxic mature NK cells, and activated CD4 effector memory T cells displaying a CTLA4 high PD1 high phenotype.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations